Magnetohydrodynamic slip flow and heat transfer over a nonlinear shrinking surface in a heat generating fluid - Deswita, Leli; Mustaqim Junoh, Mohamad; Md Ali, Fadzilah; Nazar, Roslinda; Pop, Ioan (International Journal of Engineering and Technology, 2020)
In this paper, the problem of steady slip magnetohydrodynamic (MHD) boundary layer flow and heat transfer over a nonlinear permeable shrinking surface in a heat generating fluid is studied. The transformed boundary layer equations are then solved numerically using the bvp4c function in MATLAB solver. Numerical results are obtained for various values of the magnetic parameter, the slip parameter and the suction parameter. The skin friction coefficients, the heat transfer coefficients, as well as the velocity and temperature profiles for various values of parameters are also obtained and discussed.Â